Leiomyoma of the prostate: A case report and systematic review - Wang, Shangren; Huang, Shiqiao; Pan, Yang; Ma, Yong; Kang, Jiaqi; Liu, Li; Liu, Xiaoqiang (Frontiers in Surgery, 2022)
Abstract Purpose: It is rare to find a large leiomyoma in the prostate, especially in that of a young man. This case report and systematic review provides additional information on the diagnosis, distinguishing features of imaging examinations, and treatment options. Patients and Methods: We report on the case of a thirty-year-old man with a large leiomyoma of the prostate. MRI of the prostate revealed a round mass in the posterior lobe, 8.0×8.0×5.5 cm in size. With the assistance of laparoscopy, we resected the prostate mass completely and spared this organ. A systematic review was conducted utilizing the Preferred Reporting Items for Systematic Reviews (PRISMA) including English language published reports, from 1970 to December 2021. Results: Urinary and erectile functioning was preserved postoperatively. After a year of follow-up, no evidence of recurrence emerged. A total of 21 studies were included for analysis. Conclusions: A medical history of no, or few, lower urinary tract symptoms; the characteristics of a benign tumor in imaging examinations; and negative tumor markers should be included in any differential diagnosis of leiomyoma of the prostrate. A prostate biopsy should be performed before the preparative radical prostatectomy and choose nonsurgical treatment to confirm the diagnosis. Nowadays, minimally invasive surgery is the preferred effective option for this disease. It is a rare recurrence after its removal by means of surgery.